E-LEARNING BASED ON ICARE (INTRODUCTION, CONNECTION, APPLY, REFLECTION, AND EXTENSION) ON DYNAMIC FLUID MATERIAL ASSISTED BY GOOGLE SITES: E-LEARNING BERBASIS ICARE (INTRODUCTION, CONNECTION, APPLY, REFLECTION, DAN EXTENSION) PADA MATERI FLUIDA DINAMIS BERBANTUAN GOOGLE SITES - Aisyah Nur Salsabillah; Firmanul Catur Wibowo; I Made Astra (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2025)
The utilization of technology is very helpful in supporting learning. E-learning can be used as a learning media that can create an active learning situation. This research aims to develop learning media in the form of e-learning assisted by ICARE (Introduction, Connection, Apply, Reflection, and Extension) on dynamic fluid material. The method used in this research is Research and Development (R&D) method with ADDIE model which includes five development stages, which are Analysis, Design, Development, Implementation, and Evaluation. The E-Learning developed is designed with ICARE model which includes five stages, namely: 1) Introduction, 2) Connection, 3) Apply, 4) Reflection, 5) Extension. Preliminary study that has been conducted on a number of high school students, as many as 97% stated that students more often use the internet as a learning resource. This research will be validated by material experts, media experts, learning experts, and the product will be tested on high school teachers and students. The results of this product are suggested to be a valid learning media used to facilitate students in understanding physics lessons, especially dynamic fluid material.